Mas’uliyyah and ihsan as high-performance work values in Islam - Ab.Wahab, Mastura; Ismail, Yusof (International Islamic University Malaysia, 2019)
The paper aims at explaining conceptually the work values of responsibility (mas’uliyyah) and benevolence (ihsan) in Islām based on the analysis of the principal texts in Islām, that is, the Qurʾān and the Hadith. It also elucidates the distinctive characteristics of responsibility and benevolence as Islāmic values in comparison with their non-Islāmic counterparts. More importantly, the paper argues that mas’uliyyah and ihsan are the work values of high performance in Islām. This is a conceptual paper. It is based mainly on the analysis of the Qurʾān and the Hadith, as well as the reviews of the works of Muslim scholars. The three resources of reference -- the Qurʾān, the Hadith and the works of Muslim schoars -- show consistent evidence of inclusiveness of mas’uliyyah and ihsan across environments. The findings demonstrate that both mas’uliyyah and ihsan are the key work values enabling high work performance. The findings also show that mas’uliyyah is the precondition and ihsan is the condition needed in order to achieve performance excellence. The lack of Islāmic writings on mas’uliyyah and ihsan in English restricts investigation. Despite this, the literature consulted in the study is considered sufficient to help achieve the research objectives. This paper can be considered as a pioneering work in English that discusses the Islāmic work values of mas’uliyyah and ihsan based on Islāmic sources with regard to employment relations and performance. This paper is useful to readers and researchers who are interested in gaining more knowledge about mas’uliyyah and ihsan and those who desire to empirically study and statistically test their importance on Muslim employees’ work performance.